Propagation path tracing of hydraulically created fractures based on microseismic monitoring - Hong-lei, Liu; Hai-ting, Huang; Peng-hai, Zhang; Lian-chong, Li; Jun-xu, Hou; Liao-yuan, Zhang; Zi-lin, Zhang (Frontiers in Earth Science, 2022)
To evaluate the effect of hydraulic fracturing a low permeability reservoir, a propagation-path tracing method for hydraulically created fractures was established based on microseismic monitoring data. First, the numerical simulation of the wave propagation process, grid search, and error-weight coefficient method were combined to locate the microseismic source. Then, the moment tensor inversion method was used to determine the tensile angle and source mechanism of hydraulic fracturing cracks. Next, the tensile angle was used as the weight-index to determine the size of the mixed-source mechanism fracture combined with shear and tensile source size quantization model. Finally, the spatial topological relationship between fractures was determined by comprehensively considering the spatial location and radius of the fractures, to realize the propagation-path tracing of hydraulically created fractures. These tracking results can be used as one of the bases for the evaluation of hydraulic fracturing effect.